Analisis Manajemen Risiko pada Reseller Gas LPG di Desa Mejasem Barat Kabupaten Tegal - Rahmasari, Dwi Agustina; Amirah (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Risk management is an important aspect in maintaining business continuity, including in LPG gas distribution activities, which have potential operational, safety, and supply risks. This study aims to analyze the implementation of risk management in LPG reseller businesses in Mejasem Barat Village, Tegal Regency. The focus of the study covers three main stages of risk management, namely risk identification, risk measurement, and risk management. Data was obtained through questionnaires filled out by business actors, then processed using descriptive statistical methods to produce the average value of each variable. The results of the study show that, in general, the implementation of risk management in LPG resellers in Mejasem Barat Village is in the good to very good category, especially in the aspects of risk identification and management. However, the aspect of risk measurement still needs to be improved so that LPG resellers can make more accurate risk management decisions.